2001
DOI: 10.1080/01635581.2001.9680627
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Induces Glutathione S-Transferase in Human Colon Cells and Protects From Genetic Damage by 4-Hydroxy-2-Nonenal

Abstract: Butyrate, one of the major products of gut fermentation, is known to inhibit proliferation, induce apoptosis and differentiation, and increase phase II enzyme activities in tumor cells, whereas little information is available on protective effects in less-transformed colon cells. The aim of this study was to investigate whether the chemoprotective mechanism of glutathione S-transferase (GST) induction by butyrate could also play a role in earlier stages of colon carcinogenesis and whether chemoresistance of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 35 publications
1
58
0
Order By: Relevance
“…Former studies indicated that the induction of these genes can be attributed to butyrate as the key fermentation product of dietary fiber. 28,35,41,42 Though there is no direct link between the daily recommended nut intake and FS used in the present study, we could recently confirm that the fermentation of nuts results in up to 2.8-fold higher concentrations of short chain fatty acids compared to the control and a shift of molar ratios towards butyrate production ranging in physiological observed FIGURE 3 Growth inhibiting of LT97 colon adenoma cells after incubation with fermented nut samples and controls (blank, Synergy1®) in concentrations of 2.5-20% for 24 h (a), 48 h (b), and 72 h (c) (mean + SD, n = 3). Significant differences between blank and fermentation supernatants (FS) of Synergy1® or nuts (***P ≤ 0.001, **P ≤ 0.01, *P ≤ 0.05) and between FS ( a-e P ≤ 0.05, equal letters represent significant differences) were obtained by two-way Anova/Bonferroni post-test.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies indicated that the induction of these genes can be attributed to butyrate as the key fermentation product of dietary fiber. 28,35,41,42 Though there is no direct link between the daily recommended nut intake and FS used in the present study, we could recently confirm that the fermentation of nuts results in up to 2.8-fold higher concentrations of short chain fatty acids compared to the control and a shift of molar ratios towards butyrate production ranging in physiological observed FIGURE 3 Growth inhibiting of LT97 colon adenoma cells after incubation with fermented nut samples and controls (blank, Synergy1®) in concentrations of 2.5-20% for 24 h (a), 48 h (b), and 72 h (c) (mean + SD, n = 3). Significant differences between blank and fermentation supernatants (FS) of Synergy1® or nuts (***P ≤ 0.001, **P ≤ 0.01, *P ≤ 0.05) and between FS ( a-e P ≤ 0.05, equal letters represent significant differences) were obtained by two-way Anova/Bonferroni post-test.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can lead to gene alterations causing potential tumor formation or carcinogenesis, and other pathological conditions. Increased cellular GSH is known to protect the cells from HNE-induced cytotoxicity and DNA damage (Nakajima et al, 2002;Cao et al, 2003;Ebert et al, 2001). Under oxidative stress GSH is oxidized to GSSG, which is transported out (Srivastava and Beutler, 1969;Meister et al, 1986) resulting in a significant decrease in cellular GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, GSTs are reportedly enhanced by products of gut fermentation in animals or butyrate in human colon tumor cell lines. 6 Of the members of GSTs, glutathione S-transferase theta 1 (GSTT1), and GSTM1 in particular have become a recent target of active investigation into their role in increased susceptibility to IBD, Behçet's disease (BD), or other autoimmune diseases such as primary sclerosing cholangitis when either of the two GSTTs lose their function. 2,7,8 Deletion of the GSTT1 gene, a 50 kb genomic sequence containing the entire gene located on chromosome 22q11.2, results in a GSTT1-null genotype, 5,9 fails protein synthesis, and can decrease the ability to detoxify damaging compounds.…”
Section: Introductionmentioning
confidence: 99%